ADVANCEMENTS IN SENSOR TECHNOLOGY FOR AUTONOMOUS WALKER - SEGUÍ VERDÚ, Isabel; DUNAI, Larisa; SAVA, Lilia (Journal of Engineering Science (Chişinău))
This study presents a detailed analysis of gait trajectory and orientation using Time of Flight sensors and Inertial Measurement Units during controlled movement tests in a robotic walker. The tests were performed on three distinct path configurations: straight-line, rectangular, and lemniscate paths. The Time-of-Flight sensors measured changes in distance, while the Inertial Measurement Units captured yaw and orientation data. Notably, during sharp turns, the Time-of-Flight sensors detected significant distance fluctuations corresponding to the directional changes captured by the Inertial Measurement Units yaw data. The results highlight the effectiveness of combining Time of Flight and Inertial Measurement Units data to track stable movement, detect sudden turns, and monitor orientation adjustments in complex trajectories. This combined approach can offer critical insights for gait analysis, rehabilitation, and robotics navigation.